Gender and humour: The new state of the art - Kotthoff, Helga (Linguistik Online, 2022)
The article presents a research overview on developments in the field of gender and humour over the last fifty years, going back a bit further in relation to literature and film. The research comes mainly from linguistics and communication studies, but also from sociology, psychology, literature and media studies. Most changes lie in the appropriation of multifaceted humorous forms by girls and women. Humour becomes apparent as a component of a social semiotics that indexes and stylizes (non)traditional gender poles. The sub-themes revolve around humour development in children, laughter as a form of communication, humour in the world of work and in the media.